1999
DOI: 10.4138/2026
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous barite-fluorite mineralization in the Late Devonian Kinsac Pluton, southern Nova Scotia

Abstract: Abundant barite ± fluorite ± quartz veins occur along the eastern margin of the Late Devonian Kinsac Pluton, a peraluminous granite that intruded metasedimentary rocks of the Meguma Group. The barite veins, striking 120° with vertical dip, occur in areas of strongly fractured granite, but the veins are not deformed and may contain lenses of comminuted granite. The veins (< 0.6 m wide) are dominated by coarse, cloudy white barite euhedra with or without a late infill of euhedral clear quartz and pink to dark pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The data compare well with other late Carboniferous galenas from the Kennetcook basin (Figure 10). These galenas have Pb isotopes that are similar to those of late mafic rocks, including dykes cutting Horton Group in the Kennetcook basin, late gabbro in the Wentworth pluton, and the youngest basalt in the Fountain Lake Group [7] (excluding outlier values), except [25] for Kinsac; for granites, etc., from [27,28]. [25] for Kinsac; for granites, etc., from [27,28].…”
Section: Chemistry Of Barite From Five Islandsmentioning
confidence: 98%
See 2 more Smart Citations
“…The data compare well with other late Carboniferous galenas from the Kennetcook basin (Figure 10). These galenas have Pb isotopes that are similar to those of late mafic rocks, including dykes cutting Horton Group in the Kennetcook basin, late gabbro in the Wentworth pluton, and the youngest basalt in the Fountain Lake Group [7] (excluding outlier values), except [25] for Kinsac; for granites, etc., from [27,28]. [25] for Kinsac; for granites, etc., from [27,28].…”
Section: Chemistry Of Barite From Five Islandsmentioning
confidence: 98%
“…These galenas have Pb isotopes that are similar to those of late mafic rocks, including dykes cutting Horton Group in the Kennetcook basin, late gabbro in the Wentworth pluton, and the youngest basalt in the Fountain Lake Group [7] (excluding outlier values), except [25] for Kinsac; for granites, etc., from [27,28]. [25] for Kinsac; for granites, etc., from [27,28]. Lead isotopes were determined on one galena sample (SFB87-2016) from th fractures at Five Islands.…”
Section: Chemistry Of Barite From Five Islandsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Ca-rich fluid inclusions in vein barite-fluorite hosted by the 370 Ma Kinsac Pluton (Fig. 1) originated from Carboniferous basinal fluids interacting with the Meguma Group or its detrital equivalent, the Horton Group (Kontak et al 1999b). Therefore, in the New Ross area, the Na-Ca trends in Figure 8a are related to interaction of magmatic fluids with contact metamorphic generated fluids originating from metasedimentary rocks of the Meguma Supergroup, particularly from metawackes of the Goldenville Group located in close proximity to several mineral deposits near New Ross (Turner, Walker, Morley's, Millet Brook, Long Lake).…”
Section: Metamorphic Fluidsmentioning
confidence: 99%
“…Reynolds et al (1981) reported plateau ages of 373 and 363 Ma for biotite and muscovite, respectively, and 363 Ma for biotite from two monzogranite samples from this intrusion. More recently, Kontak et al (1999b) reported a 354 Ma plateau age for K-feldspar in monzogranite from the same area.…”
Section: Previous Geochronology Of the Musquodoboit Batholithmentioning
confidence: 99%